2003
DOI: 10.1002/jhet.5570400404
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of benzohydroximinoyl chlorides and β‐(trifluoromethyl)‐acetylenic esters: Synthesis of regioisomeric (trifluoromethyl)‐isoxazolecarboxylate esters and oxime addition products

Abstract: The triethylamine induced reaction of benzohydroximinoyl chlorides, precursors of nitrile oxides, with β-trifluoromethylacetylenic esters gives rise to three products: 5-trifluoromethyl-4-isoxozolecarboxylate esters, regioisomeric 4-trifluoromethyl-5-isoxazolecarboxylate esters and an unexpected oxime 1,4-addition adduct. Product distribution is rationalized in terms of two competing reaction modes, either 1,4 addition of the oxime anion to the acetylenic ester or formation of the nitrile oxide followed by 1,3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…Preparation of C4 trifluoromethyl­isoxazole acid 35 proved to be a challenge. An initial survey of the literature revealed that the only reported method for the preparation of ester 30 occurred through a 1,3-dipolar cycloaddition reaction between ethyl trifluorobut-2-ynoate and a dipole generated in situ from N -hydroxybenzimidoyl chloride favoring the formation of the undesired isomer 31 in a ratio of 85:15 . In our hands, the reaction provided 30 , with a ratio consistent with that reported in the literature, in ∼7% yield after chromatographic separation (Scheme ).…”
Section: Chemistrysupporting
confidence: 66%
“…Preparation of C4 trifluoromethyl­isoxazole acid 35 proved to be a challenge. An initial survey of the literature revealed that the only reported method for the preparation of ester 30 occurred through a 1,3-dipolar cycloaddition reaction between ethyl trifluorobut-2-ynoate and a dipole generated in situ from N -hydroxybenzimidoyl chloride favoring the formation of the undesired isomer 31 in a ratio of 85:15 . In our hands, the reaction provided 30 , with a ratio consistent with that reported in the literature, in ∼7% yield after chromatographic separation (Scheme ).…”
Section: Chemistrysupporting
confidence: 66%
“…The isoxazole ring has been recognized as an essential heterocyclic scaffold for organic synthesis and medicinal chemistry. In particular, nearly two dozens of pharmaceuticals containing 3- or 5-methylisoxazole motif were approved by FDA to date, and many more have reached various phases of clinical studies (e.g., β-lactam antibiotics, , sulfonamide antibacterials, antidepressants, antirheumatic drugs, anti-inflammatory, antiviral, or hypoglycemic agents, fungicides, and other classes) , (Figure ). Introducing fluorine atoms into alkyl substituents is one of the most powerful design tools in drug discovery.…”
Section: Introductionmentioning
confidence: 99%
“…An initial review of the literature at the time revealed that the only reported method for the preparation of ester 6 occurred through a 1,3-dipolar cycloaddition reaction between ethyl trifluorobutyno-2-ate and a nitrile N-oxide dipole generated in situ from N -hydroxybenzimidoyl chloride­( 5 ) . Unfortunately, this reaction favored the undesired regioisomer 7 in a ratio of 85:15, as depicted in Scheme .…”
Section: Resultsmentioning
confidence: 99%